Ankle instability in sports - O`Loughlin, P. F.; Murawski, C. D.; Egan, C.; Kennedy, J. G. (The Physician and Sportsmedicine, 2009)
Ankle stability is integral to normal motion and to minimizing the risk of ankle sprain during participation in sport activities. The ability of the dynamic and static stabilizers of the ankle joint to maintain their structural integrity is a major component of the normal gait cycle. In sports, this quality assumes even greater importance given the range of movement and stresses imposed on the ankle during various sporting disciplines. In the general population, the incidence of ankle sprain is very high. In several studies, injuries to the lateral ankle ligaments have been shown to be the most common sports-related injuries, accounting for approximately 25% of all sports-related injuries. Furthermore, up to 80% of all ankle sprains involve the lateral ligament complex. Other studies have estimated their incidence as approximately 5000 injuries per day in the United Kingdom and 23 000 in the United States. Aggressive treatment of the sprained ankle is essential to maintain foot and ankle mobility and prevent prolonged disability and subsequent overuse injuries among athletes, both professional and "weekend warriors" alike.